Взаємозв'язок тривожності із рівнем самооцінки молодшого школяра - Москаленко, В.В.; Жаркова, Г.В. (My University, 2011)
Аннотация Статья посвящена исследованию взаимосвязи тревожности с уровнем самооценки младшего школьника. Работа поднимает проблематику эмоционального состояния современных школьников. Исследуется уровень тревожности и уровень самооценки 9-летних детей при помощи проективных методик. Выясняется, что у детей с высоким уровнем тревожности преобладает низкий уровень самооценки. Ключевые слова: тревожность, уровень самооценки, младший школьник, эмоциональное состояние, агрессия, неуверенность в себе. Annotation Relationship Anxiety Level of Self-Esteem of Young Schoolchildren This degree thesis is dedicated to the research of the interconnection of the anxiety with the level of selfconcept of an elementary school student. The article is devoted to the problem of emotional state of modern elementary school students. The level of uneasiness and level of a self-concept of 9-years children by means of projective techniques are investigated. We founding, that at children with a high level of uneasiness the low level of a self- concept prevails. Keywords: uneasiness, a level of self-concept, the younger schoolboy, an emotional condition, aggression, uncertainty.
Keywords: тревожность; уровень самооценки; младший школьник; эмоциональное состояние; агрессия; неуверенность в себе